The role of Foxo3a in neuron-mediated cognitive impairment - Liu, Qin-Qin; Wu, Gui-Hua; Wang, Xiao-Chun; Xiong, Xiao-Wen; Rui-Wang,; Yao, Bao-Le (Frontiers in Molecular Neuroscience, 2024)
Cognitive impairment (COI) is a prevalent complication across a spectrum of brain disorders, underpinned by intricate mechanisms yet to be fully elucidated. Neurons, the principal cell population of the nervous system, orchestrate cognitive processes and govern cognitive balance. Extensive inquiry has spotlighted the involvement of Foxo3a in COI. The regulatory cascade of Foxo3a transactivation implicates multiple downstream signaling pathways encompassing mitochondrial function, oxidative stress, autophagy, and apoptosis, collectively affecting neuronal activity. Notably, the expression and activity profile of neuronal Foxo3a are subject to modulation via various modalities, including methylation of promoter, phosphorylation and acetylation of protein. Furthermore, upstream pathways such as PI3K/AKT, the SIRT family, and diverse micro-RNAs intricately interface with Foxo3a, engendering alterations in neuronal function. Through several downstream routes, Foxo3a regulates neuronal dynamics, thereby modulating the onset or amelioration of COI in Alzheimer’s disease, stroke, ischemic brain injury, Parkinson’s disease, and traumatic brain injury. Foxo3a is a potential therapeutic cognitive target, and clinical drugs or multiple small molecules have been preliminarily shown to have cognitive-enhancing effects that indirectly affect Foxo3a. Particularly noteworthy are multiple randomized, controlled, placebo clinical trials illustrating the significant cognitive enhancement achievable through autophagy modulation. Here, we discussed the role of Foxo3a in neuron-mediated COI and common cognitively impaired diseases.